Biocompatible PBS-based copolymer for soft tissue engineering: Introduction of disulfide bonds as winning tool to tune the final properties. (December 2020) - Guidotti, Giulia; Soccio, Michelina; Gazzano, Massimo; Bloise, Nora; Bruni, Giovanna; Aluigi, Annalisa; Visai, Livia; Munari, Andrea; Lotti, Nadia
Highlights: A PBS-based random copolymer containing S-S bond was obtained by polycondensation. Fibrous scaffolds were prepared by electrospinning. Chain flexibility, crystallinity and degradability were tuned by copolymerization. Biocompatibility was confirmed by NIH-3T3 cell line growth and proliferation tests. Abstract: Thanks to the continuous progress of tissue engineering, the opportunity to overcome the main limits of traditional medicine is becoming more and more concrete. By a targeted study of biomaterials and their properties, it is possible to find ad hoc solutions for the fabrication of tissue engineered scaffolds. More in details, poly(butylene succinate) PBS is a biocompatible synthetic polymer already investigated for biomedical applications, but characterized by a high degree of crystallinity, which leads to long degradation times and mechanical properties often not suitable in the field of soft tissue engineering. In the present study, a PBS-based copolymer containing 30 mol% of dithiodipropionic co-units, P(BSBDTDP), was synthesized by two-step melt polycondensation. The comonomeric unit is characterized by the presence of -S-S- bond, potentially capable of improving both biocompatibility and biodegradability with respect to the homopolymer. After synthesis, 3D-mats and films were obtained by electrospinning and compression moulding, respectively, and then subjected to molecular, thermal and mechanical characterization. In addition, in view of a possible application in soft tissue engineering, enzymatic biodegradation studies and in vitro biocompatibility tests, using NIH-3T3 cell line, were also carried out. The results obtained show that through copolymerization solid-state properties could be nicely tailored. More in details, compared to PBS, P(BSBDTDP) is characterized by a lower crystallinity degree and mechanical properties typical of soft tissues, maintaining at the same time the good thermal stability of the parent homopolymer. In addition, copolymeric scaffold better supports cell adhesion and proliferation, undergoing degradation in biological environment slightly faster than its PBS homologous.